(untitled) (Tribhuvan Journal, 2025)
Food security has been a pressing development issue in Nepal, with agricultural land ownership playing an important role in determining household food security and availability. Land ownership patterns and food security outcomes are crucial in designing effective food security and agricultural strategies. This study has analyzed the relationship between agricultural land ownership and food security status among households in Nepal based on the results of the Nepal Living Standards Survey IV (NLSS-IV) and especially the distribution of the report in relationship to irrigations access, crop variety, and access to markets. Data in the form of households acquired in the NLSS-IV were put in the regression logistic analysis. Food consumption patterns and expenditure data were the dependent variable (household food security status (secure versus insecure). Independent variables were ownership of land, area, irrigation, index of crop diversity and Gini coefficients of market access. The investigation indicated that the land ownership greatly improved the chances of food security. The access of irrigation by households was positively associated with the odds of food security. An increase in crop diversity was also linked with a drastic improvement of food security. Food security chances were greatly increased with market access. The odds of food security were lower in rural households than in urban households. Farmland becomes a pivotal factor of the food security of the household in Nepal, which is highly empowered by the accessibility of irrigation, crop diversification, and access to the market. The results show that the ownership of land is not a sufficient factor to ensure food security unless it is coupled with other investments in the agricultural infrastructure and the market systems. The findings therefore support the total land and agricultural policies which include fair distribution of land, proliferation of irrigation facilities, encouragement of crop diversification programs and increase the rural market accessibility to enhance food security performance.